2007
DOI: 10.1088/0953-8984/19/34/346205
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the diffusion coefficient of Au in Bi-2223 superconductors

Abstract: Undoped Bi-2223 samples were prepared using a conventional solid-state reaction method. Doping of Au in Bi-2223 was carried out by means of diffusion from an evaporated Au film on pellets. We have investigated the effect of Au diffusion and diffusion-annealing duration on the microstructure and superconducting properties of Au-doped samples by performing x-ray diffraction (XRD), scanning electron microscopy (SEM), dc resistivity and critical current density measurements. Gold diffusion in Bi1.8Pb0.35Sr1.9Ca2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Among the metals Au and Ag have been found to be nonpoisoning to YBCO [9], while Ag has been found to be the only metal element that is non-poisoning to the BSCCO system [10]. In our previous works, the role of diffusion annealing time and temperature on the superconducting, structural and mechanical properties of Au diffusion-doped Bi-2223 superconductors were investigated [11][12][13][14][15]. These works indicated that gold doping enhance the superconducting and the mechanical properties of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Among the metals Au and Ag have been found to be nonpoisoning to YBCO [9], while Ag has been found to be the only metal element that is non-poisoning to the BSCCO system [10]. In our previous works, the role of diffusion annealing time and temperature on the superconducting, structural and mechanical properties of Au diffusion-doped Bi-2223 superconductors were investigated [11][12][13][14][15]. These works indicated that gold doping enhance the superconducting and the mechanical properties of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is another interesting result from Fig. 2 that the transition curves of the samples (especially for the pure one) from the normal state to the superconducting state exhibit the double-step behaviour due to the indication of weak links in the inter-granular coupling [26]. Moreover, the onset critical (T onset c ) and offset critical temperatures (T offset c ) inferred from the resistivity graphs are tabulated in Table 1.…”
Section: Electrical Resistivity Measurementsmentioning
confidence: 91%
“…Superconducting Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oy samples were prepared by the standard solid-state reaction method [25,26]. The Au evaporation (thickness of about 50 m) on one face of the samples was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no detailed work has been published on diffusion coefficient of Au in Bi(Pb)-Sr-Ca-Cu-O bulk samples. The only publication on this topic is our recent work on calculation of diffusion coefficient via lattice parameter c in Audiffused samples of Bi-2223 [26].…”
Section: Introductionmentioning
confidence: 99%